CHARACTERIZATION OF BI Γ-TERNARY SEMIGROUPS BY THEIR IDEALS - Akram, Muhammad; Kavikumar, Jacob; Khamis, Azme (Italian Journal of Pure and Applied Mathematics, 2015)
In this paper, the concept of biΓ-ternary semigroup has been introduced. The notion of biΓ-ternary subsemigroup, biΓ left (right, lateral) ideals, biΓ-quasi and biΓ-bi-ideals of this newly defined structure has been introduced. Also the regular biΓ-ternary semigroups have been studied in terms of biΓ-ideals.